Give a converse of the following expression:
[(p Λ q) V ¬r] --> ¬[(q V ¬r) --> (¬p Λ r)]

¬[(q V ¬r) --> (¬p Λ r)] --> [(p Λ q) V ¬r]

Hmmnn...

I thought I was pretty good at math, but I don't understand this question.
It almost looks more like a mathematics question than a computer science question.

Just out of curiousity: what are you studying? And what level are you?

I'm studying computer science, this is a logic question, this is my first year and I'm really confused lol

A converse of a statement P->Q is Q->P, although it does not necessarily make it true. So all you have to do is change the P and Q position. Your answer looks correct

According to my extensive knowledge of math (below are the symbols at wikipedia) the two equations will yield two different results. The --> symbol is the same is the Assembly code "if xxxxxx then" where the xxxxxx is what is before the --> symbol. So by changing the if statement you are changing what the result will be which means there is no need to examine the rest.

According to my extensive knowledge of math (below are the symbols at wikipedia) the two equations will yield two different results. The --> symbol is the same is the Assembly code "if xxxxxx then" where the xxxxxx is what is before the --> symbol. So by changing the if statement you are changing what the result will be which means there is no need to examine the rest.

Maybe so, but OP did not ask Truth value of proposition, but "what is" question. So for his question was not if the propositions follow from each other.

Thanks for the help guys n pyTony who is this he you're referring to lol?

I was referring you, more proper way would have been OP, I think. Please close your solved threads and up/down vote/give rep any answers if they seem to deserve it.

Ok will do by the way I'm a she lol